Gender equality with regard to the current challenges to Ukraine’s national security: theoretical and practical aspects (Law and Safety, 2024)
The article examines the legal and institutional mechanisms for integrating gender equality into the national security and defence sector of Ukraine. The analysis of the legal framework governing gender policy, in particular in the Armed Forces of Ukraine, is carried out. Particular attention is paid to the role of international standards, such as UN Security Council Resolution 1325 and the Istanbul Convention, in ensuring equal access of women and men to participation in defence processes.Based on theoretical analysis and empirical data, the article examines the impact of gender balance on the effectiveness of the national security sector, in particular its managerial, operational and strategic components, in the context of modern military challenges. It is found that the integration of gender equality contributes to the efficiency of the defence sector, but requires improvement of legal regulation and changes in institutional approaches.The results of the study indicate the need to revise legislative acts and introduce gender-sensitive approaches in the planning and execution of military operations. The article provides recommendations for strengthening the legal framework for gender equality in the security and defence sector of Ukraine. It is concluded that gender equality in the military does not mean mandatory establishment of equal obligations for both sexes. It is important to take into account the specifics and capabilities of each gender, ensuring equal access to military service on a voluntary basis, which is a more effective and fair approach. This allows to take into account the individual characteristics of women and men, thus ensuring the harmonious functioning of the Armed Forces of Ukraine in the context of modern challenges and needs of society.
Keywords: gender; gender equality; national security of Ukraine; defence sector; martial law; Armed Forces of Ukraine.